2021
DOI: 10.1002/jsp2.1137
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of finite element analysis for mechanical performance evaluation of intervertebral body fusion devices

Abstract: Background: Intervertebral body fusion devices (IBFDs) are a widely used type of spinal implant placed between two vertebral bodies to stabilize the spine for fusion in the treatment of spinal pathologies. Assessing mechanical performance of these devices is critical during the design, verification, and regulatory evaluation phases of development. While traditionally evaluated with physical bench testing, empirical assessments are at times supplemented with computational models and simulations such as finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…With another orthopedic implant (intervertebral body fusion devices), the FDA observed that basic information needed to assess a computational model (code verification, mesh convergence, validation, and so on) was often not included in regulatory submissions. 50 Knee device submissions likely follow a similar trend. Therefore, the computational modeling community should focus on reproducibility and more trustworthy simulations.…”
Section: An Academic Perspectivementioning
confidence: 86%
See 1 more Smart Citation
“…With another orthopedic implant (intervertebral body fusion devices), the FDA observed that basic information needed to assess a computational model (code verification, mesh convergence, validation, and so on) was often not included in regulatory submissions. 50 Knee device submissions likely follow a similar trend. Therefore, the computational modeling community should focus on reproducibility and more trustworthy simulations.…”
Section: An Academic Perspectivementioning
confidence: 86%
“…Material models and contact interactions associated with the knee (bone, cartilage, ligaments, tendons, muscles, and so on) all present challenges when evaluating model credibility and associated device performance. With another orthopedic implant (intervertebral body fusion devices), the FDA observed that basic information needed to assess a computational model (code verification, mesh convergence, validation, and so on) was often not included in regulatory submissions 50 . Knee device submissions likely follow a similar trend.…”
Section: A Regulatory Perspectivementioning
confidence: 99%
“…209,210 Model translatability concerns refer to the challenges in translating model predictions to general experimental or clinical observations, which mainly arise from the wide range of assumptions used for model development, the large variations in constitutive descriptions used to simulate tissue behavior, and the lack of a standardized process for model validation. 181,211,212 181,213 In recent years, issues centered around model translatability has become a growing concern, as a greater number of implant companies use data from finite element models for regulatory clearance purposes. 211 4 | DISCUSSION: FUTURE DIRECTIONS Decades of herniation-oriented research resulted in many important and insightful studies that identified risk factors for herniation, characterized the structure-composition-function relationship in healthy, degenerated, and herniated disc tissues, and examined mechanisms of disc failure.…”
Section: Ongoing Challenges In Finite Element Modeling Herniation Res...mentioning
confidence: 99%
“…181,211,212 181,213 In recent years, issues centered around model translatability has become a growing concern, as a greater number of implant companies use data from finite element models for regulatory clearance purposes. 211 4 | DISCUSSION: FUTURE DIRECTIONS Decades of herniation-oriented research resulted in many important and insightful studies that identified risk factors for herniation, characterized the structure-composition-function relationship in healthy, degenerated, and herniated disc tissues, and examined mechanisms of disc failure. This substantial body of work improved our understanding of herniation etiopathogenesis.…”
Section: Ongoing Challenges In Finite Element Modeling Herniation Res...mentioning
confidence: 99%
“…As described in ASME V&V40-2018 [1], model predictions relied on for decision making should be accompanied by verification and validation (V&V) evidence demonstrating simulation credibility commensurate with the risk associated with the intended model use. However, rigorous code verification evidence for medical device simulations is often omitted (e.g., see Figure 1 in [2]), in part due to the lack of detailed examples to facilitate these studies. Herein, we aim to provide such an example for superelastic nitinol.…”
Section: Introductionmentioning
confidence: 99%